Peran Mediasi Workplace Spirituality Pada Pengaruh Spiritual Leadership Terhadap Organization Citizenship Behavior - Jufrizen, Jufrizen; Nasution, Abdul Hakim (Jurnal Bisnis dan Manajemen, 2021)
The purpose of this study was to determine and analyze the influence of the Mediation Role of Workplace Spirituality on the Effect of Spiritual Leadership on Organizational Citizenship Behavior on Administrative Employees at the State Islamic University of North Sumatra, directly or indirectly. The approach used in this study is a causal approach. The population in this study were all administrative staff at the State Islamic University of North Sumatra. The sample in this study using the slovin formula totaling 66 administrative employees at the State Islamic University of North Sumatra. Data collection techniques in this study used interview techniques, documentation studies, observation, and questionnaires. The data analysis technique in this study uses a quantitative approach using statistical analysis by using the Auter Model Analysis test, Inner Model Analysis, and Hypothesis Testing. Data processing in this study using the PLS (Partial Least Square) software program. The results of this study prove that directly Workplace Spirituality on Spiritual Leadership has a significant effect on Organizational Citizenship Behavior and indirectly Spiritual Leadership has a significant effect on Organizational Citizenship Behavior mediated by Workplace Spirituality on Administrative Employees at the State Islamic University of North Sumatra.